Generating Positive Orientation in Therapy or Consultation: A Perspective Through an Article Review on Positive Psychology - Aslan, Mehmet (European Journal of Multidisciplinary Studies, 2016)
Psychology -considering a positive subjective, to some extend objective, practice of science- has been restrained and defined as a field advocated to pathological diseases, significantly when the queries for life are emerged together with feelings of desperation and pessimism, conjointly fruitfulness and senseless of life; psychological principles that we implement in therapy and consultation today weren`t much appreciated thus far. The preeminence of pathology concluded in a model of individual that is short of positive fundamentals like “hope, wisdom, creativity, future mindedness, courage, spirituality, responsibility, and perseverance” which are furthermore crucial for one`s psychological and physical well-being. Such values were disregarded or characterized as simple variations of credible negative motives. The authors are sketching an infrastructure as well as pointing our gaps in knowledge of positive psychology, and anticipating forthcoming future; expecting communities, societies, and individuals that will thrive through science and the key role of positive psychology.The aim of this study is to excavate principles, inquiries, and definitions of positive psychology to search for means andperspectives in generating positive orientation in regard with therapy and consultation, thus reviewing the article: “Positive Psychology, An Introduction” formed by two authors: Martin E. P. Seligman and Mihaly Csikszentmihalyi.